2013
DOI: 10.1111/hae.12184
|View full text |Cite
|
Sign up to set email alerts
|

Malposition and expulsion of the levonorgestrel intrauterine system among women with inherited bleeding disorders

Abstract: The levonorgestrel-releasing intrauterine system (LNG-IUS) is indicated for the management of menorrhagia and for contraception. The LNG-IUS is effective at reducing menstrual bleeding and improving haemoglobin among women with bleeding disorders. Expulsion rates for the LNG-IUS among normal women are reported to be approximately 5-10%. The aim of this study was to examine the malposition and expulsion rates of the LNG-IUS among women with inherited bleeding disorders. We conducted a retrospective study of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…If an LIUS is inserted, the expulsion rate may be higher than usual. 57 If NSAIDs are to be used for dysmenorrhea, the hematologist should know and they should be used for only a couple of days each month to avoid aggravating hemostasis with platelet dysfunction. Sometimes hematologists prescribe desmopressin acetate (DDAVP) if the teen is a DDAVP responder.…”
Section: Disorders Of Menstruation In Adolescent Girlsmentioning
confidence: 99%
“…If an LIUS is inserted, the expulsion rate may be higher than usual. 57 If NSAIDs are to be used for dysmenorrhea, the hematologist should know and they should be used for only a couple of days each month to avoid aggravating hemostasis with platelet dysfunction. Sometimes hematologists prescribe desmopressin acetate (DDAVP) if the teen is a DDAVP responder.…”
Section: Disorders Of Menstruation In Adolescent Girlsmentioning
confidence: 99%
“…Expulsion rates among women without an inherited bleeding disorder have been reported to be approximately 5%‐10% and 8% in women with IBD . In a small retrospective study, three expulsions and two device malpositions were reported among 20 women with inherited bleeding disorders . Prolonged therapy with tranexamic acid may be beneficial in preventing expulsion among these women as is the use of specific haemostatic therapies directed at controlling bleeding around the time of LNG‐IUS insertion …”
mentioning
confidence: 99%
“…The patient was also referred to a gynecologist affiliated with the hemophilia treatment centre, who inserted a progesterone-eluting intrauterine device under hemostatic coverage with desmopressin, to decrease the risk of its expulsion. 14 The patient received resources containing additional information about her illness and emergency medical treatment and was connected to the Canadian Hemophilia Society for additional support and registered for continued follow-up.…”
Section: Case Revisitedmentioning
confidence: 99%